(untitled) (Indo-Fintech Intellectuals: Journal of Economics and Business, 2024)
This study aims to test and analyze the influence of work culture, competence, and organizational commitment on employee performance with job satisfaction as an intervening variable in PT. Atalian Global Service at SMC RS Telogorejo. This research is a type of explanatory research. The population in this study is employees of PT. Atalian Global Service at SMC Telogorejo Hospital which totals 103 people. The analysis tool used is PLS-SEM using SmartPLS software. The results of the study show that work culture has a positive effect on job satisfaction. Competence has a positive effect on job satisfaction. Organizational commitment has a positive effect on job satisfaction. Work culture has a positive effect on employee performance. Competence has a positive effect on employee performance. Organizational commitment has a positive effect on employee performance. Job satisfaction has a positive effect on employee performance.